Doped zirconia and ceria-based electrolytes for solid oxide fuel cells: a review. Issue 1 (January 2012) - Mahato, Neelima; Gupta, Alka; Balani, Kantesh
Abstract : Zirconia and ceria possess fluorite-type structure and conduct electricity by means of oxide ion transport through the lattice. On doping, vacancies created at the oxygen site make way for the neighbouring oxygen atoms to 'hop' in the direction of electric field. Among doped zirconia, 8 mol% yttria-stabilized zirconia and 9–11 mol% scandia-stabilized zirconia exhibit the highest conductivity. Ceria electrolytes require lower operational temperature (~600–800°C) compared to that of zirconia electrolytes (800–1000°C). With improvement in the processing and fabrication techniques, researchers have developed thinner electrolytes to minimize ohmic polarization and enhance the ionic conductivity enabling operation at lower temperatures (~400–600°C). But such electrolytes are required to be supported on electrodes (anode or cathode) and in later times heterostructured bi-, tri- and multi-layered electrolyte films have been constructed. Since the last decade, development of submicron grain size electrolytes and ultimately two-phase materials with nanodimension grain size has shown improvement in ionic conductivity as well as low-temperature workability. The article reviews the turning points in the technological development of fluorite-based solid oxide fuel cell electrolytes from single-phase micrometer dimension grain size to recently developed two-phase nanocomposites and nanowires, and the successful achievement of its workability at low temperatures (~450°C).